Factors influencing the local skin temperature in patients with post-stroke shoulder-hand syndrome (脑卒中后肩手综合征患者局部皮温变化影响因素研究) - TANG Weiwei (汤伟伟) (中西医结合护理)
Objective To investigate the factors influencing the local skin temperature in patients with post-stroke shoulder-hand syndrome, and provide reference for implementation of targeted treatment and nursing management. Methods A cross-sectional survey was completed with a convenient sample of 88 patients with post-stroke shoulder-hand syndrome. The change of local skin temperature was evaluated by non-contact infrared thermometer. Results The palmar skin temperature of affected limb was higher than that of the contralateral limb, with a significant difference (P<0. 01). The skin temperature was not associated with gender, age or course of disease in patients with post-stroke shoulder-hand syndrome (P>0. 05). Conclusion The palmar skin temperature of affected limb was higher than that of the contralateral limb, and was not influenced by gender, age or course of disease. (目的 探讨脑卒中后肩手综合征患者局部皮温变化的影响因素, 为其后续康复的特异性对症治疗及护理提供新思路和参考依据。方法 采用方便抽样法选取2020年3月—8月医院收治的88例脑卒中后肩手综合征患者为研究对象, 采用非接触式红外体温计监测局部皮温变化。结果 肩手综合征者患侧掌内皮温高于健侧掌内, 差异有统计学意义(P<0. 01)。肩手综合征者的性别、年龄、病程与皮温无明显影响关系(P>0. 05) 。结论 脑卒中后肩手综合征患者患侧掌内皮温高于健侧, 皮温与其性别、年龄、病程无关。)